Emissions of polychlorinated dibenzo- p-dioxins and dibenzofurans from a heavy oil-fueled power plant in northern Taiwan - Wang, Ya-Fen; Chao, How-Ran; Wu, Chia-Hsin; Wang, Lin-Chi; Chang-Chien, Guo-Ping; Yang, Hsi-Hsien; Lin, Ding Yan; Tsou, Tsui-Chun (Journal of hazardous materials, 2009)
We measured the concentrations of polychlorinated dibenzo- p-dioxins and dibenzofurans (PCDD/Fs) from the flue gas and the ambient atmosphere of a power plant fueled by heavy oil in northern Taiwan. The mean emission concentration and I-TEQ concentration of total PCDD/Fs were 0.292 ng/N m 3 and 0.016 ng I-TEQ/N m 3, respectively. All PCDD/F emission concentrations in the flue gas were supposed to meet the Environmental Protection Administration Executive Yuan, R.O.C. standard (1.0 ng I-TEQ/N m 3 from 2008). Furthermore, the mean I-TEQ concentration in the ambient atmosphere was 0.011 pg I-TEQ/N m 3, which was much lower than the environmental quality standards for dioxins in Japan (0.6 pg TEQ/N m 3). Also, the PCDD/F emission factor was 0.188 ng I-TEQ/L fuel, which was comparable to the data issued in US EPA [EPA, Locating and estimating air emissions from sources of dioxins and furans, Office of Air Quality Planning and Standards, Research Triangle Park, NC, DCN No. 95-298130-54-01, 1997] (0.2 ng I-TEQ/L of fuel). Also, the result of the correlations of PCDD/Fs and operational parameters illustrated that the positively significant correlation ( r = 0.502, p = 0.048) was found only between PCDD/Fs (I-TEQ) and the flue gas emission temperature (125–157 °C). However, PCDD-TEQ/PCDF-TEQ ratios were statistically significantly associated with the decreased flue gas flow ( r = −0.659, p = 0.006), moisture ( r = −0.612, p = 0.012) and flue gas temperature ( r = −0.503, p = 0.047). For proper environmental management of dioxins, it is necessary to establish a complete emission inventory of PCDD/Fs, and, in particular, the government should pay more attention to power plants to address the information shortage.